1960
DOI: 10.1002/qj.49708637013
|View full text |Cite
|
Sign up to set email alerts
|

The variation in composition of sea‐salt nuclei with mode of formation

Abstract: It is shown that at coastal stations, while the coarser spray has a composition close to that of sea water, the smaller droplets (diameters less than about 25 microns) have a much higher proportion of potassium. The rapid decrease in the Na: K ratio with increasing distance from the sea is principally due to the settling out of the coarser spray. The result is consistent with Wilson's hypothesis that salt nuclei are formed largely from an extremely thin surface layer very rich in organic matter, which contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1961
1961
2004
2004

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Studies of bursting bubbles [Mason, 1954] have shown that a bubble of gas bursting at a liquid interface produces two types of particles: large particles from an unstable jet, which originates: from the bottom of the bubble and therefore comes from the bulk of the liquid itself, and small particles which are fragments of the shattered surface of the bubble and therefore come from the surface of the liquid. Oddie [1960] has added support to this hypothesis by collecting atmospheric nuclei of different sizes and showing that the larger particles have a Na/K ratio similar to that of bulk seawater, whereas the smaller particles are enriched in K +. Two theories have been put forward to account for the difference in chemical composition between these small particles and bulk ocean water.…”
Section: The Standard Methods Of the American Publicmentioning
confidence: 91%
“…Studies of bursting bubbles [Mason, 1954] have shown that a bubble of gas bursting at a liquid interface produces two types of particles: large particles from an unstable jet, which originates: from the bottom of the bubble and therefore comes from the bulk of the liquid itself, and small particles which are fragments of the shattered surface of the bubble and therefore come from the surface of the liquid. Oddie [1960] has added support to this hypothesis by collecting atmospheric nuclei of different sizes and showing that the larger particles have a Na/K ratio similar to that of bulk seawater, whereas the smaller particles are enriched in K +. Two theories have been put forward to account for the difference in chemical composition between these small particles and bulk ocean water.…”
Section: The Standard Methods Of the American Publicmentioning
confidence: 91%